Calcitonin gene-related peptide immunoreactive neurons with dichotomizing axons projecting to the lumbar muscle and knee in rats - Ohtori, Seiji (Springer-Verlag, 2003)
Dorsal root ganglion (DRG) neurons with dichotomizing axons have been reported in several species and are thought to be related to referred pain. However, these neurons, which have dichotomizing axons to the lumbar muscles and to the knee, have not been investigated. Clinically, pain from the lumbar muscles is sometimes referred to the lower extremities. Two kinds of neurotracers [1,1′-dioctadecyl-3,3,3′,3′-tetramethyl-indocarbocyanine perchlorate (DiI) and fluoro-gold (FG)] were used in the present double-labelling study. DiI crystals were placed in the left lower back muscle, and FG was applied to the medial side of the knee. Bilateral DRGs from L1 through L6 were immunoreacted with calcitonin gene-related peptide (CGRP) antibodies and observed under a fluorescence microscope. DRG neurons double-labelled with DiI and FG were recognized only in the ipsilateral DRGs from levels L1 to L6. Approximately 1% of DRG neurons innervating the low back muscles had other axons to the medial side of the knee. In double-labelled neurons, the ratio of CGRP-immunoreactive DRG neurons was 60%. This finding provides a possible neuroanatomical explanation for referred knee pain from the lower back since CGRP is a marker of sensory neurons typically involved with pain perception. However, these neurons are rare, and mechanisms of referred pain may be explained by the convergence–projection hypothesis.